Developing Flipbook Benadaku with YouTube videos to improve students' learning outcomes in natural and social sciences - Jannah, Nila Rohmatul; Ahmadi, Farid (Journal of Educational Management and Instruction (JEMIN), 2024)
This research was motivated by the low learning outcomes of students in natural and social sciences subjects on the material of norms in regional customs. Consequently, this study aims to develop and determine the effectiveness and feasibility of the Flipbook Benadaku media with YouTube videos to improve the learning outcomes of fourth-grade students in these subjects. Research and Development (R&D) is the type of research conducted, utilizing the research model design from Dick and Carey. The research subjects consisted of 27 fourth-grade students. To collect data, both test and non-test techniques were employed. Specifically, the test technique involved pre-tests and post-tests, while non-test techniques included observation and interviews. As a result, the development of the Flipbook Benadaku with YouTube videos was achieved. The feasibility results of the Flipbook Benadaku with YouTube videos indicate that the media is suitable for use, as evidenced by the assessments of material experts and media experts, with percentages of 92% and 90.4% respectively. Furthermore, the learning outcomes of the fourth-grade students improved significantly, with an average pretest score of 45.83 and a post-test score of 86.67, resulting in an N-gain of 0.77, which is categorized as high. Thus, the media is considered quite effective. In conclusion, Flipbook Benadaku with YouTube videos is validated as effective for use in natural and social sciences learning and can significantly enhance students' learning outcomes on the material of norms in regional customs.